Epigenetic Regulation of the Latency-Associated Region of Marek's Disease Virus in Tumor-Derived T-Cell Lines and Primary Lymphoma - Brown, Andrew C. (American Society for Microbiology, 2012)
Meq is the major Marek's disease virus (MDV)-encoded oncoprotein and is essential for T-cell lymphomagenesis. Meq and several noncoding RNAs, including three microRNA (MiR) clusters, are expressed from the repeats of the MDV genome during latent infection of T cells. To investigate the state of the chromatin in this and flanking regions, we carried out chromatin immunoprecipitation (ChIP) analysis of covalent histone modifications and associated bound proteins. T-cell lines and a lymphoma were compared. The chromatin around the promoters for Meq and the noncoding RNAs in both cell lines and the lymphoma were associated with H3K9 acetylation and H3K4 trimethylation, which are marks of transcriptionally active chromatin. These correlated with bound Meq–c-Jun heterodimers. The only binding site for Meq homodimers is located at the lytic origin of replication (OriLyt), next to the lytic gene pp38. This region lacked active marks and was associated with repressive histone modifications (H3K27 and H3K9 trimethylation). DNA CpG methylation was investigated using methylated DNA precipitation (MeDP). In cell lines, DNA methylation was abundant across the repeats but noticeably reduced or absent around the active promoters. In primary tumors, CpG methylation occurred less than 2 months after infection, focused within the ICP4 gene. These data suggest that nonrandom de novo DNA methylation occurs early in lymphomagenesis. In addition, the histone data indicate a role for Meq in the epigenetic regulation of the MDV genome repeats in transformed T cells and suggest that the OriLyt region and the Meq/MiR region might be separated by chromatin boundary elements, and preliminary data on CTCF binding are consistent with this.